Characterization of SMAD3 function in skeletal muscle growth - Ge, Xiaojia (2012)
Smad3 is a key intracellular signaling mediator for Myostatin and TGF-β1, two TGF-β superfamily members and are key regulators of skeletal muscle growth and homeostasis. Despite extensive studies about the functions and signaling of Myostatin/TGF-β1, little is known about the regulatory role of Smad3 in muscle growth. Thus the main emphasis of this thesis is to investigate the role of Smad3 in post-natal myogenesis.